Developing and validating equations to predict V˙O2 peak from the 6MWT in Childhood ALL Survivors. Issue 20 (25th September 2021) - Labonté, Jennifer; Caru, Maxime; Lemay, Valérie; Alos, Nathalie; Drouin, Simon; Bertout, Laurence; Andelfinger, Gregor; Krajinovic, Maja; Laverdière, Caroline; Sinnett, Daniel; Curnier, Daniel
Abstract: Introduction: The 6-Minute Walking Test (6MWT) is a safe, standardized and well utilized method to assess the functional capacity. Recently, it was reported that the published prediction equations cannot accurately predict a valid maximal oxygen consumption (V̇O2 peak) value in cancer survivors. Thus, the aim of this study was to establish and to validate a new equation based on the 6MWT to predict V̇O2 peak in childhood acute lymphoblastic leukemia (ALL) survivors. Methods: A total of 200 childhood ALL survivors were enrolled in this study, among which 168 participants underwent a cardiopulmonary exercise test and a 6MWT to assess their functional capacity and their cardiorespiratory fitness. In addition, participants completed a physical activity questionnaire. Participants were randomly divided in two groups to establish the equations ( n = 118 (70%)) and to validate it ( n = 50 (30%)). Multiple linear regression analyses were used to determine a new prediction equation for V̇O2 peak from 6MWT using clinical and specific variables related to the disease. The accuracy in between V̇O2 peak measured and V̇O2 peak predicted were assessed using the Bland and Altman method. Results: The new establish clinical V̇O2 peak equation is: V̇O2 peak (mL.kg −1 .min −1 ) = (−0.283*age(years)) − (0.099*weight(kg)) + (0.071*6MWD(meters)) −(0.135*HR end(bpm)) + 22.789 with a mean bias of 2.67 mL.kg −1 .min −1 (95% CI (−9.64 to 14.98)). The new establish disease-specific V̇O2 peak equation is: V̇O2 peak (mL.kg −1 .min −1 ) = (−0.236*age(years)) − (0.094*weight(kg)) −(0.120*HR end(bpm)) + (0.067*6MWD(meters)) + (0.065*MVLPA(min/day)) − (0.204*DT(years)) + 25.145 with a mean bias of 2.51 mL.kg −1 .min −1 (95% CI (−9.98 to 15.01)). Conclusion: This is the first study that predicted V̇O2 peak from a 6MWT using clinical and specific variables related to the disease of childhood ALL survivors. The availability of these newly established V̇O2 peak equations makes them an accurate tool to provide a better follow-up and better adapted physical training for survivors. We invite researchers to use our assessment procedures for their further studies. IMPLICATIONS FOR REHABILITATION: It is critical to understand the cardiorespiratory fitness of the childhood ALL survivors The maximal oxygen consumption (i.e., V̇O2 peak) is recognized as the gold standard to measure the patient's cardiorespiratory fitness in the field of exercise physiology This study is novel and reports the validation of two new VO2 peak equations, from 6MWT, by using clinical and disease-specific variables of childhood ALL survivors The availability of such validated equations can better facilitate the follow-up of survivors' cardiorespiratory fitness, by relevant health care professionals and exercise physiologists.